Connectivity of the American agricultural landscape: Assessing the national risk of crop pest and disease spread - Margosian, Margaret L.; Garrett, Karen A.; Hutchinson, J. M. Shawn; With, Kimberly A. (My University, 2009)
More than two-thirds of cropland in the United States is devoted to the production of just four crop species—maize, wheat, soybeans, and cotton—raising concerns that homogenization of the American agricultural landscape could facilitate widespread disease and pest outbreaks, compromising the national food supply. As a new component in national agricultural risk assessment, we employed a graph-theoretic approach to examine the connectivity of these crops across the United States. We used county crop acreage to evaluate the landscape resistance to transmission—the degree to which host availability limits spread in any given region—for pests or pathogens dependent on each crop. For organisms that can disperse under conditions of lower host availability, maize and soybean are highly connected at a national scale, compared with the more discrete regions of wheat and cotton production. Determining the scales at which connectivity becomes disrupted for organisms with different dispersal abilities may help target rapid-response regions and the development of strategic policies to enhance agricultural landscape heterogeneity.
Citation: Margosian, M., . . . With, K. (2009). Connectivity of the American Agricultural Landscape: Assessing the National Risk of Crop Pest and Disease Spread. Bioscience, 51, 141-151. https://doi.org/10.1525/bio.2009.59.2.7
Keywords: Geographic information systems; Graphy theory; Invasive species; Landscape connectivity; Networks